Template‐Guided Ionic Self‐Assembled Molecular Materials and Thin Films with Nanoscopic Order1. Issue 4 (2nd July 2015) - Santella, Marco; Amini, Fatima; Andreasen, Kristian B.; Aswad, Dunya S.; Ausar, Helene; Austin, Lillian Marie; Bora, Ilkay; Boye, Ida M. I.; Brinkenfeldt, Nikolaj K.; Bøe, Magnus F.; Cakmak, Emine; Catovic, Alen; et al.
Abstract: Ionic self‐assembly (ISA) is a proven method that exploits non‐covalent interactions to generate supramolecular materials. Here, we have expanded the scope of this approach fabricating thin films with nanoscopic order maintained over centimeters. Cationic layers of benzalkonium surfactants form a lamellar template. The template is able to host layers of negatively charged polyaromatic functional units, here demonstrated with β‐naphthol‐derived azo‐dyes. We show that a variety of these functional building blocks can be incorporated in the lamellar template through ISA. Sixteen different materials were produced, characterized, and processed into thin films, with lamellar order perpendicular to the substrate. Thus, a design concept is demonstrated in which diverse functional motifs can be isolated and ordered in a 2D lattice between layers of alkyl chains in bulk and in thin films, in which the molecular order is maintained and aligned to the substrate. Abstract : Come together : A general approach to make thin films with high molecular order is presented. Materials made by ionic self‐assembly between anionic functional units and cationic surfactant form highly ordered thin films upon spin‐casting.